The guide of implementing chat protocol: study case on using the socket programming concept and object-oriented programming - Alanazi, H.O.; Noor, R.M. (2010)
In the past, communication among people was limited and very difficult. Nowadays, the Internet makes our life veryeasy. Through the Internet you can easily communicate with people in different corners of the world in a few seconds. These days,the world has been converted into a small village by the Internet. The chat room is one of the effective communication tools. In thispaper, a new protocol is presented for the chat room using the socket programming concept. This protocol has been implemented using Java.